The reliability of wormlike polysaccharide chain dimensions estimated from electron micrographs - Stokke, B T; Brant, D A (Biopolymers, 1990)
Electron micrographs of alginate, xylinan, xanthan, and scleroglucan were prepared by vacuum-drying aqueous glycerol-containing solutions, and then heavy-metal, low-angle rotary replicated. Quantitative methods for excluding streamlining effects and deformation artifacts were developed and applied to the digitized polymer contours prior to analysis of stiffness. The apparent macromolecular dimensionalities were not obtainable on the basis of the change in the scaling coefficient alpha relating the rms end-to-end distance and the contour length, mean value of r2(1/2) approximately L alpha, for chains subject to the excluded volume effect in two and three dimensions. Using a two-dimensional model, the persistence length of these molecules was estimated to be (9 +/- 1) nm (alginate), (25 +/- 4) nm (xylinan), (30 +/- 4) nm (single-stranded xanthan), (68 +/- 7) nm (double-stranded xanthan), and (80 +/- 10) nm (scleroglucan). Monte Carlo calculations for wormlike chains close to an interacting surface or confined to the region between two surfaces showed that (1) strongly adsorbed molecules are essentially two-dimensional and (2) molecules restricted to the space between two surfaces separated by a distance less than 20% of the persistence length are two-dimensional in their directional correlation. The somewhat low estimates of the persistence lengths obtained from the electron micrographs compared with those reported from solution measurements can be accounted for by the adoption of a strictly two-dimensional model in the analysis, whereas the absorbed polymers are most likely intermediate between the two-and three-dimensional cases. The model calculations and the analysis of the electron micrographs suggest that stiffness parameters are obtainable from the electron micrographs when the proper theoretical description are used in the analysis.